2011
DOI: 10.3109/13880209.2011.576347
|View full text |Cite
|
Sign up to set email alerts
|

In vitroandin vivoskin anti-aging evaluation of gel containing niosomes loaded with a semi-purified fraction containing gallic acid fromTerminalia chebulagalls

Abstract: & Jiradej Manosroi (2011) Invitro and invivo skin anti-aging evaluation of gel containing niosomes loaded with a semi-purified fraction containing gallic acid from Terminaliachebula galls,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(37 citation statements)
references
References 41 publications
0
36
0
1
Order By: Relevance
“…So, the local effects of this gallic acid gel are expected to have more than that in the semipurified fraction gel. In fact, our further study (Manosroi et al, 2010c) has found that gallic acid gel cause skin irritation on rabbits' skin by the closed patch test while the semipurified fraction gel did not give this effect. In addition, when the pure gallic acid loaded in nonelastic or elastic niosomes, no rabbit skin irritation was observed.…”
Section: Gel Formulations Containingmentioning
confidence: 82%
See 1 more Smart Citation
“…So, the local effects of this gallic acid gel are expected to have more than that in the semipurified fraction gel. In fact, our further study (Manosroi et al, 2010c) has found that gallic acid gel cause skin irritation on rabbits' skin by the closed patch test while the semipurified fraction gel did not give this effect. In addition, when the pure gallic acid loaded in nonelastic or elastic niosomes, no rabbit skin irritation was observed.…”
Section: Gel Formulations Containingmentioning
confidence: 82%
“…In addition, when the pure gallic acid loaded in nonelastic or elastic niosomes, no rabbit skin irritation was observed. This may be due to the reduction of the direct contact between gallic acid and the skin when gallic acid was loaded in niosomes (Manosroi et al, 2010c).…”
Section: Gel Formulations Containingmentioning
confidence: 99%
“…Increased quercetin intake reduced circulating levels of various markers of oxidative stress: oxidized LDL, malondialdehyde, and advanced oxidation protein products (Boots et al, 2011;Egert et al, 2009;Valentova et al, 2007). Gallic acid used topically on the skin showed evidence of anti-aging activities when measured by skin elasticity (Manosroi et al, 2011). Oral consumption of green tea catechins resulted in increased concentrations of gallic acid in skin effusions and a reduced skin susceptibility to UV radiation (Rhodes et al, 2013).…”
Section: Relevance Of In Vitro Results To In Vivo Conditionsmentioning
confidence: 99%
“…accelerated wound healing in burn wounds of rats, [39] semipurified fraction containing gallic acid from T. chebula Retz. showed antiageing activity [40] and ethanol extract from fruit of this same plant protected skin against UVB photodamage. [41] The immunomodulatory results found in the present work stimulate future studies evaluating the effectiveness of AELCe in wound healing.…”
Section: Discussionmentioning
confidence: 89%